Approach to refurbishment of timber preschool buildings with a view on energy and economic efficiency - Šuman, Nataša; Žigart, Maja; Premrov, Miroslav; Žegarac Leskovar, Vesna (Journal of Civil Engineering and Management, 2019)
The refurbishment of educational buildings usually involves a variety of measures aiming at reducing energy demands and improving building functionality to achieve higher living comfort. This paper aims to develop an approach for determination of comprehensive refurbishment strategy upon existing preschool buildings in Slovenia from the aspects of energy and economic efficiency. The main idea of the approach is to separate and individually analyse the investments into those related to energy efficiency improvements and those related to improvements of building functional quality through the step-by-step evaluation of individual measures. The proposed approach was applied on the case study of the existing timber preschool building in the city of Maribor. Generally, the highest energy savings are detected only in the case of combination of multiple renovation measures. Moreover, the economic indicators show low efficiency for almost all measures if they are treated separately. Additionally, the analysis reveals that certain measures are totally inefficient in terms of energy, yet they are highly beneficial from the viewpoint of building functional quality, which indicates the importance of the multi-perspective assessment of renovation process. The conclusions of this study can be implemented to similar building types and construction ages in similar climatic and economic environments.